2011
DOI: 10.1017/s0022215111000508
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomised controlled trial comparing intense endoscopic cleaning versus minimal intervention in the early post-operative period following functional endoscopic sinus surgery

Abstract: There is no evidence from this study to support frequent endoscopic cleaning in the early post-operative period after functional endoscopic sinus surgery. Less intensive post-operative management is recommended, resulting in decreased patient morbidity and fewer post-operative follow-up appointments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This can be uncomfortable for patients particularly in the immediate postoperative period. In addition, there are a few of studies that question the benefits of early, aggressive debridement . These studies have shown no difference in outcomes in patients that underwent regular debridement compared with those that underwent minimal postoperative intervention .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be uncomfortable for patients particularly in the immediate postoperative period. In addition, there are a few of studies that question the benefits of early, aggressive debridement . These studies have shown no difference in outcomes in patients that underwent regular debridement compared with those that underwent minimal postoperative intervention .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are a few of studies that question the benefits of early, aggressive debridement . These studies have shown no difference in outcomes in patients that underwent regular debridement compared with those that underwent minimal postoperative intervention . Nonetheless, debridement, practised by many, is regarded as the cornerstone of postoperative care and is evidence based .…”
Section: Discussionmentioning
confidence: 99%
“…1327,1328 One study 1327 used a within-subject design with 1 side randomized to receive outpatient debridement at 2, 4, and 6 weeks, and the other side received no debridement. A surgeon blinded to which side was debrided assessed the endoscopic appearance at 3 months after surgery and assigned a modified endoscopic score.…”
Section: Xe2 Sinus Cavity Debridementsmentioning
confidence: 99%
“…On the contrary, the benefit of this treatment for prophylaxis of adhesions and synechiae is stressed by other sources [98], [279], [280], [281], [282]. Especially in differentiated and extended surgeries, e.g.…”
Section: “Minor” Complicationsmentioning
confidence: 99%